How Ethnoscience-Integrated Problem-Based Learning Shapes Students’ Critical Thinking: A Mixed-Methods Study - Gummah, Syifaul; Fitri, Muliana; Verawati, Ni Nyoman Sri Putu (International Journal of Ethnoscience and Technology in Education, 2026)
The study aimed to examine how ethnoscience-integrated Problem Based Learning (PBL) shapes secondary students’ critical thinking in the physics topic of work and energy and to explore the factors that support improvement. The study employed a mixed-methods design with a dominant quantitative phase followed by a qualitative explanatory phase. In the quantitative phase, a quasi-experimental nonequivalent control group pretest posttest design was implemented with an experimental class receiving ethnoscience-integrated PBL and a control class receiving expository instruction. Critical thinking was assessed through a validated test, and qualitative data were collected through observations, student artifacts, and brief reflections to explain learning processes. The experimental class achieved a moderate total n-gain of 0.70, whereas the control class showed a low n-gain of 0.27. ANCOVA results indicated a significant class effect on posttest scores after controlling for pretest, F(1, 63) = 293.27, p = 0.001, ηp² = 0.823. Qualitative findings suggested that culturally grounded problems supported problem interpretation, structured collaboration strengthened justification and analysis, teacher questioning promoted inference and revision, and comparing ethnoscience and scientific explanations fostered evaluative reasoning. The findings imply that ethnoscience-integrated PBL can strengthen critical thinking when local knowledge is used as an epistemic resource for exploration and evidence-based reasoning, supported by facilitation that makes justification and evaluation explicit during learning.